Teachers’ Difficulties in Teaching Listening Comprehension of Junior High School - Garnis, Dewi; Erlina, Dian; Husnaini (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
Listening comprehension is the most crucial part of communicating with each other. Meanwhile, in teaching listening comprehension, it is challenging for teachers because the teaching of listening comprehension has long been somewhat neglected and is often poorly taught in many EFL programs. There must be difficulties that teachers face because listening is frequently overlooked and poorly trained in the English language. In teaching listening, the teacher faced several problems, including the message, the speaker, the listener, and transcribing the words. The students cannot get the information from the listening skill. This research aimed to identify the difficulties teachers encounter in teaching listening comprehension. The study employed a qualitative research method with a case study approach. The participants in this study were English teachers at MTs Negeri 1 Jakabaring Palembang, selected through a purposeful sampling technique. The data were collected through open-ended interviews. The data were analysed using thematic analysis. The findings of this study revealed that there were six difficulties faced by teachers in teaching listening comprehension, namely: (a) students' anxiety; (b) discomfort in listening; (c) students' attitudes; (d) difficulty in controlling a large class; (e) limited teaching time in class; (f) lack of learning facilities for listening.